NS-1 antigen positive Dengue Infection and molecular characterization of Dengue Viruses in a private Medical College Hospitalin Dhaka, Bangladesh (Bangladesh Journal of Medical Science, 2018)
Introduction: Detection of dengue virus infection as soon as possible is critical for management of dengue virus infected patients. Immuno-chromatographic (ICT) tests are easy, cost effective method for dengue virus antigen detection.The sensitivity and specificity of ICT should compare with a gold standard test like RT-PCR. Aim of this study was to compare two test methods (ICT and RT-PCR), observe dengue serotype and seasonal impact on dengue infection.Methodology & result: The patients of Ibn Sina Medical College Hospital from October 2015 to October 2017 were tested for dengue NS1 antigen by ICT method. Out of 3201 sample tested 32.39% were found positive and 89 of which were re-tested for RT-PCR for comparison. Eighty eight of 89 NS1 positive cases showed positive by RT-PCR method giving an accuracy of 98.87%. Among the RT-PCR positive cases 45 were further analyzed for serotype. DEN-1, DEN-2 or both DEN- 1 and DEN-2 were found in 21, 23 and 1cases respectively. No cases of DEN-3 or DEN-4 were detected.Conclusion: This study showed that easily available and cost effective dengue NS1 antigen detection method (ICT) is as effective as molecular test (RT-PCR). DEN-1 and DEN-2 serotype were prevalent during last few years in Bangladesh. Continuous monitoring of dengue virus serotype is important for prevention and control of sudden epidemic by other serotype. Alert to be more during post monsoon when the peak of dengue virus infection was observed.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.669-673